Penerapan Teknologi Ramah Lingkungan untuk Pengolahan Rumput Laut UMKM ORA FOOD - Ani Purwanti; Satriawan D. Hariyanto; Muchlis; Suparni S. Rahayu; Fajar Y. Prabowo (Retii, 2022)
Seaweed as one of the leading commodities of the Gunungkidul Regency Government, is currently partly processed into crispy seaweed processed food by MSMEs ORA FOOD. To produce industrial-scale seaweed quality, proper handling is needed from the harvesting process to post-harvest processing. One of the processes that needs to be improved is the washing method, harvesting drying, the process of slicing processed seaweed, the process of processing waste into biogas fuel, as well as the marketing process. Washing technology using sustainable washing equipment is the right choice for MSMEs ora food. The seaweed washer uses a drive motor instead of a manual washing tool. This joint activity with partners is the framework of the PKM Grant program from the Ministry of Education and Culture for the 2022 funding year. In this activity, partners were given assistance in solutions to their problems in the form of seaweed washing machines with simple technology, seaweed slicer racks, seaweed drying machines, and biomirue digesters as a means of processing seaweed waste, as well as promotional media through the Shopee e-commerse account. In this activity, 10 MBKM students were included who were recognized for 10 credits in one year of implementing the Community Partnership Program. Keywords: seaweed, blue economy, renewable energy, appropriate technology